Dampak Hak Tanggungan terhadap Pihak Ketiga: Tanggung Jawab Kreditur dalam Praktik - rommy hardyansah (Jurnal Hukum Lex Generalis, 2025)
The right of pledge serves as a property security instrument that grants a privileged position to creditors in the event of debtor default. While this right provides legal certainty for creditors, its application can affect third parties with an interest in the secured object. This situation often leads to legal conflicts, particularly when third parties are unaware of the existence of a pledge on the acquired assets. This study aims to explore the forms of legal protection available for third parties and the legal responsibilities of creditors in the execution of the pledge. Utilizing a normative juridical method, this research analyzes regulations, principles of prudence, and the role of notaries in maintaining transparency. The findings indicate that despite existing regulations, challenges such as a lack of transparency and public awareness still hinder optimal legal protection. Therefore, measures are needed to enhance transparency in the registration of pledges and to educate the community. This study recommends regulatory improvements and increased oversight to ensure the protection of third-party rights and to establish legal certainty in transactions involving pledges.